Prioritizing Strategies for Sustainable End-of-Life Vehicle Management Using Combinatorial Multi-Criteria Decision Making Method - Ahmed, S.; Ahmed, S.; Shumon, M.R.H.; Quader, M.A.; Cho, H.M.; Mahmud, M.I. (Springer Berlin Heidelberg, 2016)
Sustainable end-of-life vehicles (ELVs) management has become a top important issue for automotive industries in many countries to tackle environmental and economic challenges. Currently, parts of the ELVs are used in many different ways, which often increase environmental hazards and reduce economic benefits. The selection of the best compromise ELVs management alternative (e.g., reuse, remanufacturing, and recycling) can bring maximum sustainability performances for any society or organization when things are to be settled professionally. The present paper proposes a multi-criteria decision-making approach using Decision-Making Trial and Evaluation Laboratory (DEMATEL) and extent analysis method on fuzzy AHP (FEAHP) to aid the decision maker in selecting the best compromise ELV management alternative with respect to the sustainable criteria. Here, DEMATEL is used to evaluate the sustainable criteria and then FEAHP is applied to evaluate the best alternatives. A case study is presented to demonstrate the applicability of the proposed approach in real-world applications. The results show that it is a viable approach and can be used as an effective tool for criteria and alternative evaluation. Finally, the implication of this study and limitations are also discussed.